Pengaruh Program Tayangan Sinetron Anak Jalanan A New Beginning Terhadap Perilaku Remaja: Studi Kasus Pada Anak Remaja Di RW 011 Kelurahan Meruya Utara - Suyudi Alimun Hakim; Mulkan Habibi (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Since ancient times, soap operas have presented many continuous stories, the content of the stories is very diverse. Many soap operas have high ratings. One of them is the soap opera that will be discussed in this research, namely the soap opera Street Children A New Beginning which aired on GTV. This soap opera has also been criticized by the Indonesian Broadcasting Commission (KPI) because there are many scenes that should not be published. The KPI believes that this soap opera contains many violations committed by teenagers. The aim of this research is to measure the street children broadcast program A New Beginning on GTV, measure the behavior of teenagers in RW 011 North Meruya Village and measure the influence of the Street Children Program A New Beginning on GTV on the behavior of teenagers in RW 011 North Meruya Village. The theories used in this research are broadcasting, broadcast media, broadcast programs, types of programs, watching and soap operas as well as adolescent behavior theory. This research uses a quantitative approach and survey research mode. The data collection technique was carried out by distributing questionnaires to 75 predetermined respondents. Sampling used the Startified Random Sampling Technique. This research is shown by the average value of respondents' answers for variable (X) of 3.63, this value is classified as high (Agree) and the average value of respondents' answers for variable (Y) is also classified as high (Agree) at 4.03. The quite large influence of soap opera program broadcasts on adolescent behavior can also be assessed at the (R) correlation of 0.806 which is classified as very high and R square 0.649 or 64.9% influence while the remaining 35.1% is influenced by other factors.